CORPORATE RISK-TAKING DAN TAX AVOIDANCE - mediatrix, maria (Jurnal Ekonomi dan Pariwisata, 2016)
ABSTRACT The purpose of this study to determine the effect of corporate risk-taking against tax avoidance . The samples using purposive sampling technique . Analysis of study data using linear regression . The analysis showed that the corporate risk-taking effect on tax avoidance . The higher the corporate risk- taking, it will lower the tax avoidance , which is indicated by the high cash efective tax ratio . Keywords : Corporate Risk -Taking , Tax Avoidance . ABSTRAK Penelitian ini memiliki tujuan untuk mengetahui pengaruh corporate risk-taking terhadap tax avoidance. Penentuan sampel menggunakan teknik purposive sampling. Analisis data penelitian menggunakan regresi linear. Hasil analisis menunjukkan bahwa corporate risk-taking berpengaruh pada tax avoidance. Semakin tinggi corporate risk-taking, maka tax avoidance akan semakin rendah, yang ditunjukkan dengan tingginya cash efective tax ratio . Kata kunci: Corporate Risk-Taking, Tax Avoidance.